Comparative transcriptome analysis of oil palm flowers reveals an EAR-motif-containing R2R3-MYB that modulates phenylpropene biosynthesis - Li, Ran (BMC Plant Biol, 2017)
BACKGROUND: Oil palm is the most productive oil crop and the efficiency of pollination has a direct impact on the yield of oil. Pollination by wind can occur but maximal pollination is mediated by the weevil E. kamerunicus. These weevils complete their life cycle by feeding on male flowers. Attraction of weevils to oil palm flowers is due to the emission of methylchavicol by both male and female flowers. In search for male flowers, the weevils visit female flowers by accident due to methylchavicol fragrance and deposit pollen. Given the importance of methylchavicol emission on pollination, we performed comparative transcriptome analysis of oil palm flowers and leaves to identify candidate genes involved in methylchavicol production in flowers. RESULTS: RNA sequencing (RNA-Seq) of male open flowers, female open flowers and leaves was performed using Illumina HiSeq 2000 platform. Analysis of the transcriptome data revealed that the transcripts of methylchavicol biosynthesis genes were strongly up-regulated whereas transcripts encoding genes involved in lignin production such as, caffeic acid O-methyltransferase (COMT) and Ferulate-5-hydroxylase (F5H) were found to be suppressed in oil palm flowers. Among the transcripts encoding transcription factors, an EAR-motif-containing R2R3-MYB transcription factor (EgMYB4) was found to be enriched in oil palm flowers. We determined that EgMYB4 can suppress the expression of a monolignol pathway gene, EgCOMT, in vivo by binding to the AC elements present in the promoter region. EgMYB4 was further functionally characterized in sweet basil which also produces phenylpropenes like oil palm. Transgenic sweet basil plants showed significant reduction in lignin content but produced more phenylpropenes. CONCLUSIONS: Our results suggest that EgMYB4 possibly restrains lignin biosynthesis in oil palm flowers thus allowing enhanced carbon flux into the phenylpropene pathway. This study augments our understanding of the diverse roles that EAR-motif-containing MYBs play to fine tune the metabolic flux along the various branches of core phenylpropanoid pathway. This will aid in metabolic engineering of plant aromatic compounds. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12870-017-1174-4) contains supplementary material, which is available to authorized users.